Concrete Formwork Safety and Local Practice - Whyte, Andrew; Brandis, Paul (Engineers Australia, 2012)
Accident prevention is a primary concern for the construction industry; formwork is a major anxiety.Recent formwork failures locally have been as significant as a permanent structural failure. Whilstmany formwork failures concern practice discrepancies, their occurrence may also stem from a more fundamental cause; investigations here seek to address guidance and legislation governing formwork practice locally. Documentation governing Australian formwork is examined alongside industry perceptions of the current situation. Findings highlight a limitation in using legislative-based models of control, and a need to reassess formwork-design education and training.